Perylene nanostructured films optimization for organic electronics: Molecular, structural, and electrochemical characterization - Garcia, Melina P.B. [UNESP]; Martin, Cibely S. [UNESP]; Kavazoi, Henry S. [UNESP]; Maximino, Mateus D. [UNESP]; Alessio, Priscila [UNESP] (Elsevier, 2023)
The deposition technique, structure, and thermal treatment can influence the optical and electrical properties of perylene derivatives films. In this work, the nanostructured Langmuir-Schaefer films of bis(n-propylimide) perylene (PTCD-Pr) with thermal treatment were optimized for an electrochemical application. The PTCD-Pr film before and after thermal treatment was characterized by ultraviolet-visible absorption, infrared absorption spectroscopy, micro-Raman scattering, and voltammetry. Brewster angle microscopy images confirmed the higher aggregation degree of molecules on Langmuir film. The PTCD-Pr deposition showed a linear growth, forming H, J, and null aggregates. The infrared absorption spectroscopy indicates a preferential head-on orientation with a slight chromophore deviation. After thermal treatment (200 °C for 2 h), the PTCD-Pr film showed a decrease in the contribution of null aggregates while maintaining the same molecular orientation. The Raman and surface-enhanced Raman spectroscopy measurements also confirmed the presence of PTCD-Pr molecules distributed throughout the substrate surface, and the thermal treatment conditions did not degrade the PTCD-Pr molecule. Moreover, thermal treatment contributes to the increase of stability of the film at the electrode surface for electrochemical measurements. In the presence of active species (paraquat in this case), the thermally treated film showed promising electrocatalytic properties compared to the unmodified electrode.
Keywords: Film characterization; Nanostructured thin films; Paraquat; Perylene